Comparative characteristic of standards of the optical density of bone tissue in the periapical region at persons of young age - A. F. Yusupova; L. P. Gerasimova; I. N. Usmanova; A. P. Sorokin (Эндодонтия Today)
Тhe relevance of the research topic. Among the most important and not completely solved problems of therapeutic dentistry is the problem of full diagnosis and quality of endodontic treatment of patients with chronic periodontitis. Purpose. Determination of the norm of the optical density of bone tissue in the periapical region in the normal chewing groups of teeth in young people. Methods — to determine the parameters of the optical density in the focus of destruction, the data of radiovisiography and dental computed tomograms were analyzed. 68 people aged 20-30 years, with various forms of chronic apical periodontitis without endodontic intervention in the anamnesis were examined. Results.Тhe structure of the bone tissue of the upper and lower jaw has a different density, on dental computed tomography the density is 10-15 times higher than on radiovisiography, which is due to the peculiarities of the measurement program. Summary. The analysis of methods of radiovisiography and dental computed tomography allowed to determine the average values of normal optical density of bone periapical area of the masticatory groups of teeth of the upper and lower jaw, which are important in monitoring the quality of endodontic treatment of chronic forms of periodontitis.